The Real Direction of Dancy’s Moral Particularism* - Wall, Edmund (Journal of moral philosophy, 2011)
Jonathan Dancy, who defends a version of moral particularism, is committed to the view that any feature or reason for action might, in logical terms, have a positive moral valence in one context, a negative moral valence in a different context, and no moral valence at all in yet another context. In my paper, I attempt to demonstrate that, despite the denial by Dancy that proposed grounding properties with invariant moral valences may play a foundational role in morality, his own approach toward moral reasoning unknowingly assumes such foundational grounding properties. I argue that Dancy’s moral particularism is unknowingly directed toward moral absolutism, and, in making that argument, uncover reasons, admittedly inconclusive, to favor an absolutist ethic.